Republic of Kosovo : Second and Third Reviews under the Stand-By Arrangement, and Request for Program Extension-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Kosovo. (IMF Staff Country Reports; Country Report, 2017)
This paper discusses Kosovo's Second and Third Reviews under the Stand-by Arrangement, and Request for Program Extension. Economic performance remains positive, with growth estimated at 3.5 percent in 2016 and projected at similar levels in 2017. Fiscal deficits remain contained, with strong tax revenues limiting the impact from rising pensions for war veterans. All performance criteria and indicative targets for December 2015 and June 2016 were met with comfortable margins. Given this progress, the IMF staff supports the authorities' request for the completion of the second and third reviews.